Training of occupational safety and health: knowledge among healthcare professionals in Malaysia - Lugah, V.; Ganesh, B.; Darus, A.; Retneswari, M.; Rosnawati, M.R.; Sujatha, D. (2010)
Introduction: Awareness of occupational safety and health (OSH) plays an important role in the prevention of occupational injuries and diseases. Following the enactment of the Occupational Safety and Health Act (OSHA) in 1994, various programmes have been implemented by different agencies to increase awareness and knowledge of OSH in the workplace, including among healthcare workers. The objective of this study was to determine the level of OSH awareness and knowledge among healthcare professionals in Malaysia. Methods: A cross-sectional study was conducted using a 21-item self-administered questionnaire addressing information on demographics, general OSH issues, OSH legislations, occupational hazards in the healthcare setting and personal protective equipment (PPE). Results: The response rate was 93.1 percent (284 healthcare professionals). The overall level of knowledge on OSH was moderate, with a mean score of 62.0 percent. A larger proportion of doctors showed good OSH knowledge compared to other categories of healthcare workers, with administrative staff scoring the poorest marks. Participants were most knowledgeable about PPE, with a mean score of 72.0 percent (95 percent confidence interval CI 68.3, 75.6), compared to other sections such as general OSH, legislations and occupational hazards, with mean scores of 58.0 percent (95 percent CI 56.1, 60.1), 57.0 percent (95 percent CI 54.1, 60.8) and 64.0 percent (95 percent CI 61.7, 66.2), respectively. Conclusion: Although the OSHA 1994 has existed in Malaysia for more than ten years, awareness of OSH remains relatively poor. This warrants a greater effort to promote OSH knowledge and principles among the professionals.